(untitled) (Fiep Bulletin - online, 2011)
The Inclusion of the People with Special Needs is being a discussion object the last years and raisin for different perspectives, especially in the classes of Physical education. The present work looked for to identify as the students’ service with Physical Deficiency is being accomplished and to contemplate about the possibilities of including in the classes of Physical education, leaving of the beginning that the school needs to dispose objectively to assure the access and the students’ permanence of all, because it only is not enough to the same to accept, if the teachers, the other professionals or even the school community if they don’t prepare for her accomplishment. In the year of 2004, 219 students existed with Special Needs registered at 50 schools of the State Net of Teaching of Boa Vista - RR. The method, in the investigation field, is characterized as to the research - action, with sample composed by 11 teachers of Physical education, where they were applied written questionnaires, containing five (5) questions related to the inclusive school Physical education and the practice in the respective classes, interviews, observations and dialogue with the teachers on the approached theme. To present research it looked for to demonstrate that there is possibility to work the inclusive education in the physical education classes, leaving of the beginning that the students’ inclusion with physical deficiency in the school and in all of the activities that she propitiates, it is a to "do educational" fair, however this inclusion should provide appropriate conditions so that, like this, the student can have more possibilities to develop their potentialities. The school should be willing to receive and, mainly, to develop this new system, because it only is not enough to the same to accept the professionals and the school community are not still prepared for her accomplishment.